PENGARUH PENAMBAHAN KACANG KEDELAI PADA PROSES PEMBUATAN SNACK BAR BERBAHAN DASAR AMPING - Tritisari, Angga (PPPM POLTESA, 2024)
Agriculture in Indonesia has great potential and as one of the key sectors in national development and development, economic development of a region can be done by creating quality products based on the resources of the region, one of which is processing amping into snack bar products. The aim of this research is to identify the chemical properties and formulate the right ones to produce snack bars made from rice amping. This type of experimental research with snack bar products consists of three formulas with a ratio of whole amping and soybean flour, namely A1 (90 grams and 10 grams), A2 (80 grams and 20 grams), and A3 (70 grams and 30 grams). The snack bar product that has the best value for fat and protein content is sample A3 with 70 grams of whole amping and 30 grams of soybean flour. Of all the snack bar formulas, the right formula is the formula with the addition of 70 grams of whole amping and 30 grams of soybean flour, because the ingredients needed in snack bars are high protein and fat content to increase energy.